Influencing mobile banking acceptance among consumers in Malaysia - Yen, Yuen Yee; Hui, Dianne Goh Ming (Asian Economic and Financial Review, 2023)
The adoption of mobile banking in Malaysia is low despite the government’s efforts to digitalize the national banking system. Malaysian citizens are uncomfortable embracing mobile banking due to the absence of adequate knowledge-based trust. As only 54.2% of Malaysians are willing to adopt mobile banking in daily life, this research was conducted to boost mobile banking acceptance. This study empirically investigates attributes influencing mobile banking acceptance in Malaysia. New attributes of mobile banking acceptance, such as perceived competence, perceived benevolence and perceived integrity, have been examined in this study to address the acceptance problems faced by the banking industry and customers. The purposive sampling method was used where the targeted respondents must have prior experience in mobile banking. The data was collected using an adapted questionnaire, and a total of 385 valid responses were analyzed. For hypothesis testing, structural equation modeling (SEM) was used to confirm the relationship between variables. Perceived ease of use, perceived relative advantage, perceived compatibility, perceived competence, perceived benevolence, and perceived integrity were found to have a significant effect on mobile banking acceptance. Understanding the impact of new constructs, such as perceived competence, perceived benevolence and perceived integrity, benefits banking institutions, policy makers and mobile commerce practitioners in addressing problems relating to mobile banking acceptance.